Detection of Rouge waves from Space - Lehner, Susanne; Rosenthal, Wolfgang; Schulz-Stellenfleth, Johannes; Niedermeier, Andreas; Nieto-Borge, Jose Carlos (2003)
Space borne Synthetic aperture radar are able to provide high resolution measurements of ocean waves on a global scale. SAR is still the only instrument providing directional information on waves on a continuous basis in the open ocean. The present study uses a reprocessed data set of complex SAR images acquired by the European Remote Sensing satellite ERS-2 to estimate different wave parameters relevant for ship security. In addition, a new method is presented to derive two dimensional sea surface elevation fields from complex SAR data. The method permits to analyze wave fields in more detail than conventional SAR wave measurement techniques, which only estimate the wave spectrum. The technique provides parameters like maximum to significant wave height ratios, wave steepness, or the probability of wave breaking. Global maps and statistics of the new parameters are presented